Glucose Functionalized Magnetic Iron Oxide Nanoparticles for Protein Detection and Separation (Journal of Scientific Research, 2024)
Iron oxide magnetic nanoparticles (MNP) are considered to be emergent nanoparticles for magnetic separation and MRI imaging probes. Here, glucose-functionalized iron oxide (γ-Fe2O3) magnetic nanoparticles have been prepared for specific protein detection and separation. First, hydrophobic iron oxide (γ-Fe2O3) was synthesized by standard organometallic approaches, and the same has been converted to soluble, colloidally stable, hydrophilic primary amine (-NH2)-PEG terminated iron oxide (γ-Fe2O3) nanoparticles using reverse micelle based robust polyacrylate coating chemistry. Then, glucose was covalently linked to this amine (-NH2)-PEG terminated iron oxide (γ-Fe2O3) nanoparticles by using glutaraldehyde-based coupling chemistry. Finally, glucose-functionalized iron oxide (γ-Fe2O3) nanoparticles have been used for specific detection and separation of a glycoprotein, Concanavalin-A.